Hubungan Kompetensi Semantis dan Kemampuan Menulis Cerpen Siswa Kelas X SMAN 1 Lengayang - Mega, Nasri; Emidar, Emidar; Nursaid, Nursaid (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purpose of research is to describes: (1) semantic competenty, (2) writing short story ability, and (3) the relationship between semantic and students class X SMAN 1 Lengayang, regency ability in writing short story. This research is quantitative research by using descriptive method. Population in this research is class X SMAN 1 Lengayang about 290 students. Sample is 15% from 290 students is 42 students by using random sampling technique. Based on the result of the research can be concluded: (1) semantic competency 66-75 % is more than enough. (2) writing short story ability about 66-75 % is more than enough. (3) there is positive relationship and significant between semantic competency and students ability in writing short story of class X SMAN 1 Lengayang.